The effect of using personal-level indoor air cleaners and respirators on biomarkers of cardiorespiratory health: a systematic review. (January 2022) - Liu, Shuo; Wu, Rongshan; Zhu, Yutong; Wang, Tong; Fang, Jiakun; Xie, Yunfei; Yuan, Ningman; Xu, Hongbing; Song, Xiaoming; Huang, Wei
Graphical abstract: Abstract: Background: Emerging studies have investigated potential cardiovascular and respiratory health impacts from the use of personal-level intervention equipment against air pollution exposure. The objective of this systematic review is to assess the efficacy of personal-level air pollution intervention on mitigating adverse health effects from air pollution exposure by using portable air cleaner or wearing respirator. Methods: In this systematic review, we searched PubMed and Web of Science for published literatures up to May 31, 2020, focusing on personal-level air pollution intervention studies. Among these studies, we investigated the impacts on cardio-respiratory responses to the use of these interventions. The intervention of review interest was the use of personal-level equipment against air pollution, including using portable air cleaner indoors or wearing respirator outdoors. The outcome of review interest was impacts on cardio-respiratory health endpoints following interventions, including level changes in blood pressure, heart rate variability (HRV), lung function, and biomarkers of inflammation and oxidative stress. Weighted mean differences or percent changes were pooled in meta -analyses for these health endpoints. The heterogeneity across studies was assessed using the Cochran's Q-statistic test, and the individual study quality was assessed using the Cochrane risk of bias tool version 2 (RoB 2). We further applied the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) method to evaluate the certainty of evidence. Results: From systematic literature search and screening, we identified 29 related eligible intervention studies, including 21 studies on indoor portable air cleaner use and 8 studies on respirator use. For portable air cleaner intervention, we observed suggestive evidence of beneficial changes on cardio-respiratory health endpoints. Collectively in these studies, we found significantly beneficial changes of 2.01% decreases (95% CI: 0.50%, 3.52%) in systolic blood pressure, as well as non-significantly beneficial changes of 3.04% increases (95% CI: -2.65%, 8.74%) in reactive hyperemia index and 0.24% increases (95% CI: −0.82%, 1.31%) in forced expiratory volume in 1 s. We also observed non-significant reductions in levels of inflammation and oxidative stress biomarkers, including C-reactive protein, interleukin-6, fibrinogen, fractional exhaled nitric oxide and malondialdehyde. For respirator intervention, we observed some beneficial changes on cardiovascular health endpoints, such as significant increases in HRV parameters [SDNN (2.20%, 95% CI: 0.54%, 3.86%)], as well as non-significant decreases in blood pressure [SBP (0.63 mmHg, 95% CI: −0.39, 1.66)]; however, no sufficient data were available for meta -analyses on lung function and biomarkers. RoB 2 assessments suggested that most intervention studies were with a moderate to high overall risk of bias. The certainty of evidence for intervention outcome pairs was graded very low for either portable air cleaner or respirator intervention. The common reasons to downgrade study evidence included loss to follow-up, lack of blinding, lack of washout period, small sample size, and high heterogeneity across studies. Conclusions: The uses of indoor portable air cleaner and respirator could contribute to some beneficial changes on cardiovascular health, but with much limited evidence on respiratory health. Low certainty of the overall study evidence shed light on future research for larger sample size trials with more rigorous study design.